Seismic Fragility Assessment of an Isolated Multipylon Cable-Stayed Bridge Using Shaking Table Tests - Yutao Pang (Advances in Civil Engineering)
In recent decades, cable-stayed bridges have been widely built around the world due to the appealing aesthetics and efficient and fast mode of construction. Numerous studies have concluded that the cable-stayed bridges are sensitive to earthquakes because they possess low damping characteristics and high flexibility. Moreover, cable-stayed bridges need to warrant operability especially in the moderate-to-severe earthquakes. The provisions implemented in the seismic codes allow obtaining adequate seismic performance for the cable-stayed bridge components; nevertheless, they do not provide definite yet reliable rules to protect the bridge. To date, very few experimental tests have been carried out on the seismic fragility analysis of cable-stayed bridges which is the basis of performance-based analyses. The present paper is aimed at proposing a method to derive the seismic fragility curves of multipylon cable-stayed bridge through shake table tests. Toward this aim, a 1/20 scale three-dimensional model of a 22.5 m cable-stayed bridge in China is constructed and tested dynamically by using the shaking table facility of Tongji University. The cable-stayed bridge contains three pylons and one side pier. The outcomes of the comprehensive shaking table tests carried out on cable-stayed bridge have been utilized to derive fragility curves based on a systemic approach.